Successful aging and preventative health: a business owner's perspective - Bell, Joshua (My University, 2024)
Successful aging can be viewed as a continuous and ongoing holistic process or as a goal-oriented approach. Both views provide sufficient exploration and definition toward development continuing through adulthood into the latter. However, the investigation of successful aging and how its definition can become affected by technological-based health innovation is an under-researched topic. Using literature and qualitative interview findings, successful aging may be considered to also incorporate the use of health-related innovation assets under the umbrella of preventative health, which contributes as an important factor toward how older individuals perceive the success of themselves and the various areas of their life as they continue to develop in late adulthood.
Keywords: successful aging; preventative health; health innovation; development